2021
DOI: 10.1364/oe.430319
|View full text |Cite
|
Sign up to set email alerts
|

Thermocavitation: a mechanism to pulse fiber lasers

Abstract: In this paper, we present a novel mechanism for the generation of laser pulses based on the phenomenon of thermocavitation. Thermocavitation bubbles were generated within a glass cuvette filled with copper nitrate dissolved in water, where the tip of an optical fiber was placed very close to the bubble generation region. Once the bubble is generated, it expands rapidly and the incoming laser light transmitted through the optical fiber is reflected at the vapor-solution interface and reflected back into the fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…When the tip of the optical fiber is placed in the solution, and there is no generation of microbubbles, the amount of light reflected toward the fiber is minimal. However, the amount of reflected light increases during the microbubble generation, as previously reported [13]. Therefore, the duration of the pulses is directly related to the growth and collapse time of the microbubble.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…When the tip of the optical fiber is placed in the solution, and there is no generation of microbubbles, the amount of light reflected toward the fiber is minimal. However, the amount of reflected light increases during the microbubble generation, as previously reported [13]. Therefore, the duration of the pulses is directly related to the growth and collapse time of the microbubble.…”
supporting
confidence: 73%
“…Recently, Zaca-Morán et al reported the generation of pulses in optical fiber lasers using the phenomenon of thermocavitation [13]. Thermocavitation bubbles were created by irradiating a highly absorbent solution of copper nitrate dissolved in water with a CW laser (λ= 980 nm) using laser power from 75 to 400 mW.…”
mentioning
confidence: 99%